Students’ Perceptions of Intrinsic Factors Influencing Motivation in Speaking Classes - Antika, Ruli; Nailul Authar; Edi Pujo Basuki; Mujad Didien Afandi; Novi Rahmania Aquariza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study explores students’ perceptions of intrinsic motivational factors that influence their participation in English speaking classes at an Indonesian junior high school. Based on Self-Determination Theory and self-concept in language learning, the study focuses on competence, autonomy, and self-concept as key factors affecting students’ willingness to speak. Using a descriptive qualitative design, this research involved 48 students at a junior high school in Ponorogo, East Java, Indonesia, with 25 students selected for semi-structured interviews after data saturation was reached. Data were collected through classroom observations and interviews over four weeks and analyzed using thematic analysis. The findings show that competence was the most dominant factor, reported by 21 students, or 84%, as students felt more motivated when they completed speaking tasks successfully and received constructive feedback. Autonomy was reported by 18 students, or 72%, showing that topic and peer selection increased engagement. Self-concept was identified by 15 students, or 60%, indicating that students’ positive image of themselves as future English speakers reduced anxiety and encouraged participation. This study concludes that competence, autonomy, and self-concept interact as a motivational triad that strengthens students’ intrinsic motivation in speaking classes.